The Role of the Teacher in Motivating Student Learning in the Basic Subjects of the Class X Audio Video 1 Expertise Program at SMK Negeri 4 Medan - Sukarman Purba; Rizka Wanda Fiana Lubis; Ahmad Danil Lubis; Ananda Hutagaol (Indonesian Journal of Educational Science and Technology, 2023)
This research aims to determine the teacher's role in motivating student learning in the basic subject of the Class X Audio Video 1 Expertise Program at SMK Negeri 4 Medan. The sample in this study were Class X Audio Video 1 students consisting of 25 students. Data collection was carried out using interview, observation and questionnaire techniques. From the observations it was concluded that the teacher has a very important role in student learning motivation. Because it can be seen from the number of students who pay attention to the teacher's explanation and are interested in ongoing learning. From the results of the interviews it can be concluded that the Audio Video teacher is someone who is firm and carries out his role as a teacher who motivates students in learning activities so that students have high motivation when participating in class learning. From the overall results of the questionnaire students' learning motivation is in the high category with an average acquisition of 62.5%. Thus, it was concluded that the students were in good condition in terms of getting motivation from their teachers. High learning motivation will affect student learning outcomes. When students feel motivated, they tend to be more focused, persistent, and committed to achieving their goals.